2004
DOI: 10.1111/j.1365-201x.2004.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular volumes during exercise in endurance athletes assessed by contrast echocardiography

Abstract: By using contrast echocardiography, a large increase in stroke volume in endurance athletes could be explained by an almost linear increase in end-diastolic volume and an initial small decrease in end-systolic volume during incremental upright exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 19 publications
4
24
0
Order By: Relevance
“…The inconsistent results of previous studies [4-7,11,12,14,26] may be explained by differences in imaging modalities and, perhaps most important, body position. The results of this study are in line with other studies of supine exercise showing unchanged LVEDV [5,9,10,27,28].…”
Section: Discussionmentioning
confidence: 83%
“…The inconsistent results of previous studies [4-7,11,12,14,26] may be explained by differences in imaging modalities and, perhaps most important, body position. The results of this study are in line with other studies of supine exercise showing unchanged LVEDV [5,9,10,27,28].…”
Section: Discussionmentioning
confidence: 83%
“…A previous study reported that the O2 pulse was equivalent to the stroke volume calculated echocardiographically at the maximal HR during ramp exercise. 18 Therefore, we believe that the O2 pulse substantially reflects the stroke volume and is a parameter of cardiac function during exercise. It is generally known that HR is 2-to 3-fold higher at maximum exercise than at rest, despite only 1.5-to 2-fold increase in stroke volume.…”
Section: Discussionmentioning
confidence: 99%
“…The athletes also participated in a third exercise test for volume measurements, which has been described previously (Sundstedt et al, 2004). To summarize, LV volume measurements were performed from the apical view by using contrast echocardiography.…”
Section: Volume Measurementsmentioning
confidence: 99%
“…volume per time, was calculated by dividing the stroke volume, assessed in a previous study (Sundstedt et al, 2004), by the filling time. volume per time, was calculated by dividing the stroke volume, assessed in a previous study (Sundstedt et al, 2004), by the filling time.…”
Section: Filling Ratementioning
confidence: 99%